Effect of root conditioning agents hyaluronic acid, EDTA and chlorhexidine on the attachment of human gingival fibroblasts to healthy root surface - Walaa Babgi; Mashael Alhajaji; Lujain Al-Mehmadi; Rokaia Elbaqli; Noha Khayat; Salwa Aldahlawi; Abdel-Rahman Youssef (Elsevier, 2021)
Background: The gold standard treatment of periodontal diseases is scaling and root planing (SRP). Different adjunctive root conditioning agents such as hyaluronic acid (HA), ethylenediaminetetraacetic acid (EDTA), and chlorhexidine (CHX) have been used with SRP to improve the smear layer removal and the healing of periodontal tissues. The aim of this study was to compare the effect of manual scaling with or without HA, EDTA, or CHX root conditioning on the attachment and viability of human gingival fibroblasts (GF). Methods: Fifteen healthy single rooted teeth were co llected and divided randomly into a scaled (n = 12) and non-scaled control group (n = 3). The scaled roots were subdivided equally into four groups; the first group did not receive any chemical treatment, while the remaining groups were treated with the conditioning agents HA or 17% EDTA or 0.2% CHX gel. Gingival fibroblasts were seeded on the top of each root and incubated for 48 h to allow attachment to the roots. The viability of fibroblasts attached to the root surface was assessed using MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) cell viability assay. Results: The cell viability was the highest in the scaled only group (p = 0.0001) while the lowest was in the scaled with EDTA group (p > 0.05). The scaled group was the highest followed by the HA and CHX groups, while the EDTA group showed the lowest mean value. Conclusion: SRP remains the superior method for regaining cell attachment to the root surface, leading to better periodontal health, and adjunctive therapies did not enhance the GF attachment to the root surface beyond the effect of SRP. Further studies are needed to investigate the effect of root conditioning agents on periodontally diseased teeth in vitro and compare them in vivo.